TWO DYNAMICS OF EUROPEANIZATION: THE CASE OF CROATIA AND SLOVAKIA - FRUZSINA SIGÉR (Köz-gazdaság, 2020)
Horvátország és Szlovákia utóbbi két évtizede igen eltérő európaizációs dinamikát mutat. Horvátország belekeveredett a jugoszláv háborúba és két EU-bővítési kört is kihagyott. Szlovákia néhány „elvesztegetett év” után felzárkózott a visegrádi országokhoz és elsőként vezette be közülük az eurót. A két ország kezdeti feltételeiben számos hasonlóság mutatkozik. A két eset összehasonlítása rávilágít arra, hogy milyen feltételek mellett valószínűbb, hogy egy ország európaizál és egyes kormányok miért tesznek intézkedéseket az EU elvárásainak teljesítése érdekében, míg mások nem. Croatia and Slovakia show two very different dynamics of Europeanization in the past two decades. Croatia got involved into the Yugoslav war of succession and missed two rounds of EU enlargements. After some “wasted years”, Slovakia caught up with the Visegrád countries and became the first country to introduce the Euro among them. The initial conditions of the two countries are similar from number of aspects. The comparison of the two cases highlight under what conditions is a country more likely to Europeanize than the other and why do governments implement measures in order to fulfil EU requirements and why others do not.